A Minimalist Analysis of Lexical Aspect in Persian - Mousa Ghonchepour (̒Ilm-i Zabān, 2022)
This article studies stative, activity, accomplishment and achievement lexical aspects based on evidence from Persian and represents aspectual tree diagrams for them. Data analysis shows that events have various stative-dynamic interpretations. Internal argument does not play any role in stative aspectual events and collocation of these events with durative adverbs indicates their atelic and lack of aspectual interpretation domain while internal argument contrary to external one plays a role in aspectual interpretation of dynamic activity, accomplishment and achievement events. [±quantity] of internal argument against definite or indefinite argument has an effect on aspectual interpretation of events. Aspectual projection and [±telicity] of an event are located on predication phrase and external argument is out of aspect and domain of aspectual interpretation. Activity events have only the aspectual feature while the achievement and accomplishment events holds both and aspectual features. These events contrary to stative events have no aspectual features.  The and aspectual features of accomplishment events are located on different nodes having structural dominance on each other while the and aspectual features of achievement events are located on one node and they have no dominance on each other. The variability of lexical aspect between dynamic and static events and the ambiguous aspectual interpretation of activity-achievement and activity-accomplishment events proves that lexical meaning of verbs does not play a role in determining lexical aspect. Moreover, the existence of two different structures for the same meaning confirms that lexical aspect is syntactic.